Scoping Review: Analysis of Alcohol Levels in Food and Beverages Using Gas Chromatography - Suryanto, Suryanto; Muslikh, Faisal Akhmal; Purwitasari, Neny; Ma’arif, Burhan (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v2i0.1843, 2022)
Islamic teachings explain that food or beverage should not be consumed with more than 0.5% alcohol because it is categorized as khamr, which is unlawful. In determining the levels of foods or beverages that contain alcohol, one of which is the gas chromatography method with several aspects of the method validation used. So that it can be seen how halal food or beverage is. The purpose of this scoping review is to map the available evidence related to the optimum conditions of analysis of alcohol content in a food product by gas chromatography and obtain a method of analyzing alcohol content in food products with several parameters validation methods, including selectivity, linearity, the limit of detection, precision, and accuracy. This scoping review has followed the framework of Arksey and O'Malley, which consists of identifying the problem formulation from the literature review; seeking relevant evidence; completing studies of relevant scientific articles; mapping data; conclude and reporting results. PRISMA flowchart diagram is used for the flow of evidence search. The results of this review show that there are 6 research articles obtained from the database. This review shows that the analysis of alcohol content using the gas chromatography method has high sensitivity, accuracy, validity, and recovery. It is hoped that this scoping review can be used as a reference and theoretical basis in analyzing food products using the gas chromatography method with several aspects of validity.